Changing and Improving Behavior in Management and Team Meetings: A Case History From the Portuguese Banking Sector - Farinha, João; Tomé, Eduardo (My University, 2019)
This case history critically reflects upon the implementation of an OCD initiative designed to improve the efficiency and productivity of management meetings and team meetings within one part of a large multinational financial bank situated in Portugal. It describes why the initial change strategy failed, and how a subsequent evidence-based approach to change agency practice helped bring about more effectively the desired improvements in the behavior and performance of managers and staff when attending meetings.